2016
DOI: 10.1002/mus.24913
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged static stretching on motor unit firing properties

Abstract: Despite reduced motor unit firing rates following the stretches, the motor control scheme remained unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For each MU, 2 parameters were extracted from the firing rate data: (1) recruitment (REC) thresholds [expressed relative to MVC (%MVC)]; and (2) peak firing rate (PFR) at the targeted contraction level during the first, middle, and final seconds of the steady force segment (pps). A 1,000‐ms Hanning window was used to smooth the mean firing rate (MFR) curve (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…For each MU, 2 parameters were extracted from the firing rate data: (1) recruitment (REC) thresholds [expressed relative to MVC (%MVC)]; and (2) peak firing rate (PFR) at the targeted contraction level during the first, middle, and final seconds of the steady force segment (pps). A 1,000‐ms Hanning window was used to smooth the mean firing rate (MFR) curve (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies indicate that the time of exposure to muscle stretching also influences the absolute strength. Ye et al (15) found a decrease in static absolute strength for the biceps brachii after a 100 second static muscle stretch. Arruda et al (16) , submitted 11 young men to passive stretching statically for 40 seconds and found strength reduction in the 10RM test when compared to the group that only performed warm-up.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, it is essential to point out that our findings and those of the works cited here refer to techniques that do not use Proprioceptive Neuromuscular Facilitation (PNF). That is because studies show controversial results when using PNF, in which shorter exposure times caused substantial decreases in resistance strength and strength (15) . In short, we believe that any flexibility technique (including PNF) that reaches the plastic phase of the muscle, applied immediately before RT, results in decreased resistance force impacting the subject's acute performance.…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al . (2016) measured motor unit activity during trapezoidal contractions at 30% and 70% MVC torque before and after 12 repetitions of 100 s stretch (20 s rest) of the biceps brachii. However, MVC torque was assessed immediately after the stretch protocol and was significantly reduced relative to before stretching.…”
Section: Discussionmentioning
confidence: 99%